2004
DOI: 10.1086/383018
|View full text |Cite
|
Sign up to set email alerts
|

Stellar and Gaseous Abundances in M82

Abstract: The near-infrared (near-IR) absorption spectra of starburst galaxies show several atomic and molecular lines from red supergiants that can be used to infer reliable stellar abundances. The metals locked in stars give a picture of the galaxy metallicity prior to the last burst of star formation. The enrichment of the new generation of stars born in the last burst can be traced by measuring the hot gas in the X-rays. For the first time, detailed stellar abundances in the nuclear region of the starburst galaxy M8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 47 publications
8
75
1
Order By: Relevance
“…They attributed the weakness of the nitrogen-bearing molecules to the low nitrogen abundance in these galaxies, based on the observed trend in the HCN/HCO + ratio with metallicity. The weak J HCN 4 3 =  emission observed in M82 may be a similar effect, as there is some evidence of sub-solar metallicity for this galaxy (e.g., Origlia et al 2004;Nagao et al 2011).…”
Section: Variation In the Infrared-molecular Line Luminosity Ratiomentioning
confidence: 71%
“…They attributed the weakness of the nitrogen-bearing molecules to the low nitrogen abundance in these galaxies, based on the observed trend in the HCN/HCO + ratio with metallicity. The weak J HCN 4 3 =  emission observed in M82 may be a similar effect, as there is some evidence of sub-solar metallicity for this galaxy (e.g., Origlia et al 2004;Nagao et al 2011).…”
Section: Variation In the Infrared-molecular Line Luminosity Ratiomentioning
confidence: 71%
“…Origlia et al (2004) measured the nuclear gaseous and stellar metallicities by using X-ray and near-infrared spectroscopic observations, and they found that both metallicities are close to or slightly less than the solar metallicity in M 82. Taking the metallicity gradient into account, these metallicities (based also on diagnostics little affected by dust extinction) are consistent with the metallicity inferred through the far-IR fine-structure diagnostics.…”
Section: Comparison With Observational Datamentioning
confidence: 99%
“…In this paper, we focus on stars with solar initial composition (X = 0.7, Z = 0.02). This choice is partly motivated by the high metallicity of the starburst galaxy M 82 -with Z Z (McLeod et al 1993;Origlia et al 2004;Mayya et al 2006) -which contains one of the most promising candidate ULXs, M 82 X-1, and that may host a black hole of intermediate mass, as argued by e.g. Ptak & Griffiths (1999); Kaaret et al (2001); Matsumoto et al (2001); Strohmayer & Mushotzky (2003), but see Okajima et al (2006) for arguments in favour of a stellar mass black hole in M 82 X-1.…”
Section: Introductionmentioning
confidence: 99%